SYSTEMATIC ORGANIZATION OF PROCESSES OF DEVELOPMENT OF SPIRITUAL AND SOCIAL ACTIVITY IN STUDENTS AND YOUTH AS AN ACTUAL SOCIAL AND PEDAGOGICAL PROBLEM - Rakhmanova M. Q. (Bright Mind Publishing, 2025)
This article covers the theoretical and methodological foundations of the systematic organization and effective management of the processes of formation and development of spiritual and social activity in students. It also analyzes the socio-pedagogical tasks facing the modern education system, the methods used in pedagogical research, the interdisciplinary approach, the importance of constructive and methodological knowledge, and the content of pedagogical laws. The study also shows the role of methodological approaches aimed at the comprehensive development of the student's personality, increasing their social activity, step-by-step educational technologies and experimental research. The article serves to find solutions to urgent problems in education by combining modern pedagogical theory and practice.
Keywords: Spiritual and social activity, systematic approach, pedagogical process, modern education, methodological foundations, didactic principles, student personality, constructive methodology, pedagogical research, educational technology.